Food waste (FW) in concessioned sodas of a Public University in Heredia, Costa Rica - Rojas-Vargas, Julián (2020)
Around 815 million people suffer from hunger in the world and of these 39 million people suffer from this problem in Latin America and the Caribbean. About one third of the food produced in the world is lost or wasted. According to the FAO, these figures are on the rise, showing that climate change, bad practices in agriculture and food waste jeopardize food security and sovereignty. Therefore, the objective of this work was to determine the loss and waste of food (PDA) with respect to the daily production of food, for the identification of strategies that minimize or solve the PDA in the sodas of the Omar Dengo Campus. Food waste was measured in the different sodas of the Omar Dengo Campus of the University, with a standardized methodology established by the Costa Rican Network for the Reduction of Food Loss and Waste and the SAVE FOOD® initiative. Significant differences were obtained in the PDA values ​​generated by the sodas. Characteristics such as the type of population and good practices in the kitchen cause less food waste. It is concluded that you must work with the users of the sodas through awareness campaigns on the subject of waste to reduce the percentages so high presented in the area of ​​return in dishes.